COMPARISON OF EFFICACY AND TOLERABILITY OF ORIGINAL AND GENERIC DRUGS OF SIMVASTATIN IN PATIENTS WITH HYPERLIPIDAEMIA AND HIGH RISK OF ISCHEMIC HEART DISEASE COMPLICATIONS - S. N. Tolpygina; S. Y. Martsevich (Рациональная фармакотерапия в кардиологии)
Aim. To assess efficacy and safety of generic simvastatin, Simvahexal, in comparison with original drug of simvastatin, Zocor, in patients with hyperlipidaemia in short-term study.Material and methods. 30 patients (19 men and 11 women, 64,0±1,8 y.o.) with low density lipoprotein (LDL) cholesterol ≥3,0 mmol/l and high cardiovascular risk were involved into the study. During 5 weeks before study including patients kept the hypolipidaemic diet and did not receive any hypolipidaemic drug. 28 patients completed study, 2 patients drop out: one patient because of nettle rash on Zocor therapy, another one – because of personal reason. Efficacy was assessed by dynamic of lipid profile and a number of patients who reached target level of LDL cholesterol (<3 mmol/l). Safety was assessed by side effect rate registration. Patients were randomized in 2 groups (G1 and G2): G1 patients (n=15) received Zocor 20 mg/day during 6 weeks, G2 patients (n=15) – Simvahexal 20 mg/day. After 6 weeks of therapy G1 patients were switched from Zocor to Simvahexal, G2 patients did not change their therapy. Simvahexal dose was increased to 30 mg/day, if the target level of LDL cholesterol had not been reached after first 6 weeks of therapy.Results. After switching therapy from Zocor to Simvahexal 11 patients increased the dose to 30 mg/day, 3 patients kept the dose of 20 mg/day, 1 patient drop out. At the beginning of the study 15 patients received Simvahexal 20 mg/day, after 6 weeks the dose was increased to 30 mg/day in 8 patients, 7 patients kept the dose of 20 mg/day. After 6 weeks of therapy with Zocor 20 mg/day levels of the total cholesterol (TC) and LDL cholesterol reduced on 25,2% and 33,6% (p<0,001), respectively. Next 6 weeks of therapy with Simvahexal in the average dose of 27,7 mg/day this reduction reached to 30,9% and 39,9% (p<0,001), respectively. After 6 weeks of therapy with Simvahexal 20mg/day levels of the TC and LDL cholesterol reduced on 28,2%and 38%(p<0,001), respectively. Next 6weeks of therapywith Simvahexal in the average dose of 25,3mg/day this reduction reached to 29,6%and 42,5%(p<0,001), respectively. In G1 patients Zocor 20mg/day reduced atherogenesis index (AI) from5,2 to 3,3 (p<0,001) after 6weeks of therapy. Next 6weeks of therapywith Simvahexal in the average dose of 27,7mg/day this reduction reached to 3,1. In G2 patients AIwas reduced from4,1 to 2,4 (p<0,001) after first 6 weeks of therapy with Simvahexal 20 mg/day and remained at the same level during next 6 weeks of therapy. Both drugs were comparable in rate (6 cases for each) and intensity of side effects. Slight increase (in the normal range) of creatine kinaze, alanine aminotransferase and aspartate aminotransferase levels was observed during both therapies, but a little bit more prominent in Simvahexal one.Conclusion. Simvahexal, is comparable with Zocor in terms of hypolipidaemic effect in 6-week therapy.We consider Simvahexal® as a generic therapeutically equivalent to original simvastatin drug.